Effect of Oral Versus Intramuscular Vitamin D Replacement on Oxidative Stress and Outcomes in Traumatic Mechanical Ventilated Patients Admitted to Intensive Care Unit. (5th September 2019) - Hasanloei, Mohammad Amin Valizade; Rahimlou, Mehran; Eivazloo, Afsoon; Sane, Shahryar; Ayremlou, Parvin; Hashemi, Reza
Abstract: Background: This study aimed to evaluate the safety and efficacy of 2 forms of vitamin D supplementation on oxidative stress and weaning from the ventilator in patients with traumatic injury and vitamin D deficiency. Methods: Seventy‐two patients were randomly divided into 3 groups: receiving 50, 000 IU pearl cholecalciferol daily for 6 days, 1 intramuscular injection of 300, 000 IU of cholecalciferol, or a control group that did not receive any supplement. Duration of mechanical ventilation, body composition, and biochemical biomarkers were measured before and after the intervention. Result: At the end of the study, the mean serum 25(OH)D increased in the intervention groups compared with the control group ( P  < .05). The interleukin 6, erythrocyte sedimentation rate, C‐reactive protein levels, Sequential Organ Failure Assessment score, duration of mechanical ventilation, and length of intensive care unit admission significantly decreased; however, total antioxidant capacity concentration did not differ significantly between the 2 intervention groups. Among the body composition variables, extracellular water ratio changes were statically different in oral vitamin D group compared with the control group ( P  = .001). No side effects were reported with the supplements. Conclusions: Vitamin D administration improved clinical signs and biochemical biomarkers in a small group of patients with traumatic injury. Well‐designed multicenter clinical studies with longer intervention duration are necessary for this field.